Defect Promoted Capacity and Durability of N‐MnO2–x Branch Arrays via Low‐Temperature NH3 Treatment for Advanced Aqueous Zinc Ion Batteries. Issue 47 (14th October 2019) - Zhang, Yan; Deng, Shengjue; Luo, Mi; Pan, Guoxiang; Zeng, Yinxiang; Lu, Xihong; Ai, Changzhi; Liu, Qi; Xiong, Qinqin; Wang, Xiuli; Xia, Xinhui; Tu, Jiangping
Abstract: Defect engineering (doping and vacancy) has emerged as a positive strategy to boost the intrinsic electrochemical reactivity and structural stability of MnO2 ‐based cathodes of rechargeable aqueous zinc ion batteries (RAZIBs). Currently, there is no report on the nonmetal element doped MnO2 cathode with concomitant oxygen vacancies, because of its low thermal stability with easy phase transformation from MnO2 to Mn3 O4 (≥300 °C). Herein, for the first time, novel N‐doped MnO2– x (N‐MnO2– x ) branch arrays with abundant oxygen vacancies fabricated by a facile low‐temperature (200 °C) NH3 treatment technology are reported. Meanwhile, to further enhance the high‐rate capability, highly conductive TiC/C nanorods are used as the core support for a N‐MnO2– x branch, forming high‐quality N‐MnO2– x @TiC/C core/branch arrays. The introduced N dopants and oxygen vacancies in MnO2 are demonstrated by synchrotron radiation technology. By virtue of an integrated conductive framework, enhanced electron density, and increased surface capacitive contribution, the designed N‐MnO2– x @TiC/C arrays are endowed with faster reaction kinetics, higher capacity (285 mAh g −1 at 0.2 A g −1 ) and better long‐term cycles (85.7% retention after 1000 cycles at 1 A g −1 ) than other MnO2 ‐based counterparts (55.6%). The low‐temperature defect engineering sheds light on construction of advanced cathodes for aqueous RAZIBs. Abstract : With a facile hydrothermal process and subsequent low‐temperature (200 °C) NH3 treatment, N‐doped MnO2– x (N‐MnO2– x ) branch arrays with concomitant oxygen vacancies are fabricated on conductive TiC/C backbones to form N‐MnO2– x @TiC/C core/branch arrays. By virtue of an integrated conductive framework, enhanced electron density, and increased surface capacitive contribution, the designed N‐MnO2– x @TiC/C arrays cathode exhibits excellent electrochemical performance in zinc ion batteries.